Peran Kepuasan Pelanggan dalam Memediasi Pengaruh Pemasaran Hubungan Pelanggan dan Citra Merek Terhadap Loyalitas Pelanggan Starbucks Coffee - Nabila Putri Maharani; Cinthya Bella (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the role of customer satisfaction in mediating the influence of customer relationship marketing and brand image on customer loyalty at Starbucks Coffee in Lampung. The research adopts a quantitative approach using a survey method. Data were collected from 210 respondents who are Starbucks customers and belong to Generation Z, using purposive sampling. The results show that customer relationship marketing and brand image have a positive and significant effect on customer loyalty. In addition, both variables also significantly influence customer satisfaction. Customer satisfaction itself is proven to have a positive and significant effect on customer loyalty. Furthermore, the mediation test indicates that customer satisfaction partially mediates the relationship between customer relationship marketing and brand image on customer loyalty. These findings imply that strengthening customer relationships and maintaining a positive brand image are essential strategies to enhance customer satisfaction and ultimately foster customer loyalty. This study contributes to the development of marketing literature, particularly in the coffee shop industry, by highlighting the importance of customer satisfaction as a mediating variable in shaping customer loyalty behavior among Generation Z consumers.